The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3897/natureconservation.17.9714
|View full text |Cite
|
Sign up to set email alerts
|

Conservation genetics of American crocodile, Crocodylus acutus, populations in Pacific Costa Rica

Abstract: Maintaining genetic diversity is crucial for the survival and management of threatened and endangered species. In this study, we analyzed genetic diversity and population genetic structure at neutral loci in American crocodiles, Crocodylus acutus, from several areas (Parque Nacional Marino Las Baulas, Parque Nacional Santa Rosa, Parque Nacional Palo Verde, Rio Tarcoles, and Osa Conservation Area) in Pacific Costa Rica. We genotyped 184 individuals at nine microsatellite loci to describe the genetic diversity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…More recently, a study on populations of C. acutus in the Greater Antilles and the Americas recognized distinguishable phylogenetic relationships and high genetic divergence between these two groups [36]. C. acutus populations along the Pacific coast of Costa Rica exhibited small to moderate levels of inbreeding and significant levels of population differentiation potentially attributed to the lack of connectivity between some localities and the occurrence of population bottlenecks in the past [37]. In addition, Pacheco et al [33] extensive sampling throughout Mexico revealed several unique lineages as a result of historical and present hybridization between C. acutus and C moreletti.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a study on populations of C. acutus in the Greater Antilles and the Americas recognized distinguishable phylogenetic relationships and high genetic divergence between these two groups [36]. C. acutus populations along the Pacific coast of Costa Rica exhibited small to moderate levels of inbreeding and significant levels of population differentiation potentially attributed to the lack of connectivity between some localities and the occurrence of population bottlenecks in the past [37]. In addition, Pacheco et al [33] extensive sampling throughout Mexico revealed several unique lineages as a result of historical and present hybridization between C. acutus and C moreletti.…”
Section: Introductionmentioning
confidence: 99%